ANALISA HUKUM ASURANSI KENDARAAN BERMOTOR MENURUT KITAB UNDANG-UNDANG HUKUM DAGANG - Aringga, Rino Dedi (Yayasan Education and Social Center, 2024)
In motor vehicle consumer financing activities usually involve three parties. First, the creditor as a business entity that carries out financing for the procurement of installments for consumer needs (motorcycles or cars) with an installment or periodic payment system. Second, debtors as customers who receive financing facilities from creditors for the purchase of motor vehicles. Third, dealers as companies that provide consumer goods (motorcycles or cars) in the context of consumer financing. The relationship between risk and insurance is a close relationship with one another. From a risk management perspective, insurance is even considered as one of the best ways to handle a risk. In article 246 of the KUHD, the limitations of the insurance agreement are as follows: Insurance or coverage is an agreement, where an insurer binds himself to an insured, by asking for a premium, to provide compensation to him for a loss, damage, loss of expected profit, which may be suffered by an unspecified event